IMPROVING THE ENERGY EFFICIENCY OF THE DRYING PROCESS IN A 2-CHAMBER DRYER - Paziuk, Vadym; Vyshnievskyi, Vitalii (Collection of scientific papers «ΛΌГOΣ», 2025)
Increasing the energy efficiency of drying plant materials in the created 2-zone chamber dryer is achieved through the installation of manufactured thick-film heating electric elements and the use of partial recirculation of the coolant - 60% of the heated coolant after drying is returned to the dryer, and 40% is emitted into the atmosphere. The main objective of the study is to determine the drying kinetics and specific heat consumption during the operation of a 2-zone chamber dryer.